Analisis Deforestasi Dan Hak Hidup Flora Sebagai Subjek Ekologis Dalam Tafsir Al-Qur’an: Analysis of Deforestation and the Right to Life of Flora as Ecological Subjects in the Interpretation of the Qur'an - Yuni Khairani; Lukmanul Hakim; Nixson Nixson; Nur Azimah; Luthfi Kurnia Wildani (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2025)
This study aims to examine the right to life of flora as ecological subjects within the framework of thematic Qur’anic exegesis and to formulate a new eco-theological paradigm to address deforestation and its global implications. The employed methodology is qualitative and interpretative, with descriptive analysis of three key verses: QS. ar-Rahman: 6, QS. al-An‘am: 99, and QS. al-Baqarah: 205. Empirical deforestation data from Indonesia (KLHK, GFW) are integrated with classical and contemporary exegeses to understand the position of plants in the Qur’anic cosmology. Findings reveal that the Qur’an positions flora not merely as passive objects but as spiritual beings that prostrate, sources of divine mercy, and entities whose right to life must be preserved. This eco-theological concept affirms plants as subjects of worship, ecosystem supporters, and moral entities within the divine order. The study develops a thematic eco-theological exegesis framework that combines up-to-date deforestation data with Qur’anic analysis, offering an interdisciplinary perspective for environmental conservation. Limitations include a textual scope confined to three verses and the absence of field verification; future research is recommended to incorporate quantitative surveys of affected communities and extend textual analysis to relevant hadith and additional Qur’anic verses on environmental preservation.